PENGARUH PENYIMPANAN PADA SUHU RENDAH TERHADAP UMUR SIMPAN DAN TOTAL BAKTERI AIR SUSU IBU ( ASI ) - Aminah, Siti; Isworo, Joko Teguh (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2004)
Mother's milk is a fat emulsion in protein, lactose and organic salts which is secreted by both mother bosom gland, as  especialis food to baby.  Giving of mother's milk until 4 month of the baby's age ( exclusive ASI)  have fulfilled requirement of food to  baby. To mothers work, giving of exclusive ASI (mother's milk) is unworkable  properly.One of the alternative to be able to give ASI fully by  conducting  of storage ASI at low tentperoture. Results of research  indicated  that  there  was  change  which striking  at colour, flronta, acidity (pH) and  consistency up to the fourth days of storage. Change of cotrsistency  and aroma happened at the fifth days of storage, this matter showed that the  duration  of storage of ASI at the low temperature is 4 day. Analysis to  total of bacteria indicated  that the duration of storage do not have an effect on total of bacteria of ASI kept.